Marketing Strategy Analysis Of Consumer Purchase Interest In The Covid-19 Pandemic Laksmi Kebaya Store Lampung - Sriyani, Ni Wayan Dewi; Ardansyah, Ardansyah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Marketing strategy is a set of goals and objectives, policies and rules that give direction to the company's marketing efforts from time to time, at each level and its references and allocations, especially as the company's response to the changing environment and competitive conditions. This study aims to analyze marketing strategies in increasing consumer buying interest at the Laksmi Kebaya store in Lampung. The research method used is descriptive qualitative research method using SWOT analysis technique. The data collection method used is using observation and interviews. The benefit of this research is to add insight into the importance of understanding marketing concepts, as a reference in dealing with the same problem later and become important input for companies in knowing marketing strategies for consumer buying interest. Based on the results of the SWOT analysis, it can be concluded that the strength factor analysis of the Laksmi Kebaya store has a score of 1.92 and the weakness factor has a score of 1.27, so that the total internal score of the company is 3.19 while the results of the opportunity factor of the Laksmi Kebaya shop have a score of 1. 58 and threats have a score of 1.37 so that the total score on external factors is 2.95. From the results of the analysis of these factors, the Laksmi Kebaya shop is in the first quadrant position, namely the Growth strategy (development strategy).